Long‐term maternal cardiometabolic outcomes 22 years after gestational diabetes mellitus. Issue 4 (20th February 2020) - Tutino, Greg E; Tam, Claudia HT; Ozaki, Riza; Yuen, Lai Yuk; So, Wing Yee; Chan, Michael HM; Ko, Gary TC; Yang, Xilin; Chan, Juliana CN; Tam, Wing Hung; Ma, Ronald CW
Abstract: Aims/Introduction: Women with gestational diabetes mellitus are at increased risk for type 2 diabetes. We characterized the association between maternal glycemia during pregnancy with long‐term outcomes. Methods and Methods: In this prospective nested case–cohort study, participants were recalled for follow up with detailed evaluation including oral glucose tolerance test at 8, 15 and 22 years. Logistic regression was used to estimate the risk of developing impaired glucose tolerance/type 2 diabetes and metabolic syndrome at follow up. The association between maternal glycemia at pregnancy and follow up was evaluated by linear regression. We also charted trajectory of β‐cell function during follow up. Results: The analysis included 121 women with a mean follow‐up period of 22.5 years, and a mean age of 50.3 years. Gestational diabetes was associated with an adjusted odds ratio of 2.48 (95% confidence interval 1.03–5.99) for combined diabetes/impaired glucose tolerance at follow up ( P  = 0.04). Women with a pre‐pregnancy body mass index ≥23 had an odds ratio of 5.43 (95% confidence interval 1.87–15.72) for metabolic syndrome at follow up, compared with those with body mass index <23 ( P  = 0.002). Both fasting and 2‐h glucose during pregnancy were strongly associated with glycemic indices at follow up ( P‐ value <0.001–0.016). Gestational diabetes was associated with impaired β‐cell function that remained relatively stable after the index pregnancy. Conclusions: Chinese women with a history of gestational diabetes have a high prevalence of impaired glucose tolerance/type 2 diabetes at 22‐year follow up. Glucose levels during mid‐pregnancy are strongly associated with those of middle age. Abstract : In this long‐term follow‐up of women with GDM, we found that 2‐hour glucose during OGTT at pregnancy predicted β‐cell function (as measured by ODI) 22 years post‐partum. Results of 2‐hour glucose during OGTT at pregnancy is a more useful indicator of long‐term metabolic risk. Most of the cases which later converted to type 2 diabetes occurred within the first 15 years postpartum.